PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA PENGRAJIN ANYAMAN PURUN DESA LAMPIHONG KABUPATEN BALANGAN - Mailiana Mailiana; Diana Hayati (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2017)
Abstract,The role of woven craftsmen in the economy is a source of income for some people in Lampihong sub-district, but it can also be seen from the aspect of job potential and give positive influence to other businesses, such as raw material suppliers and shops as distributors.The subject of this research is woven craftsmen purun located in district Balangan. Some of the reasons for the selection of the subject of this research are the first woven craftsmen only apply the production management, the marketing management of financial management and accounting in a very simple way in which they run the activities with the knowledge management that they have so far that has been applied for many years and hereditary without there is additional knowledge and improvement. Both the lack of tithing and training obtained by the craftsmen woven purun so that the results of their operations so far do not show encouraging progress.Some of the problems faced by craftsmen include problems that lie in the performance of wicker craftsmen in the balangan district, namely in poor product quality, product design is less varied, marketing areas are still limited due to weak marketing strategy, financial management is still very simple and knowledge about very low accounting. Some solutions that can be offered to overcome this problem is to provide education, counseling and training to woven craftsmen purun about production management in terms of improving product quality, product design more varied, calculation of cost of production, management of raw materials and production systems more efficient. Counseling and training on marketing management is the improvement of its main marketing strategy of product improvement, promotion, pricing and expansion of marketing area. Counseling and training in the field of financial management is an improvement in financial management and in the field of accounting is about the recording of expenditures and revenues and the preparation of a simple bookkeeping.